Orthodontic biomechanics with intermaxillary elastics - Marcel Marchiori FARRET (Dental Press Editora, 2023)
ABSTRACT Introduction: Intermaxillary elastics are orthodontic resources widely used in various malocclusions. Their main advantages are low cost, easy insertion and removal by patients, and application versatility. As main disadvantages, we can highlight the need for cooperation from patients and the side effects normally present in treatments with this resource. Knowledge of the biomechanics involved in the use of intermaxillary elastics is essential to take full advantage of the desired effects and avoid unwanted effects in their use. Objective: Therefore, the objective of this article is to describe the anchorage preparation, connection methods, time and force of use, and side effects involved in the use of intermaxillary elastics for the treatment of anteroposterior, vertical and transverse problems. For that, clinical cases and biomechanics schemes will be presented, in which all these details will be described.